Muchtar Lutfi's Thoughts on Religion And National Understanding (1931-1950) - Suryani, Wulan Agitha; Jarudin, Jarudin; Kaksim, Kaksim (PT. Hafasy Dwi Nawasena, 2024)
This study discusses Muchtar Lutfi's Thoughts on Religion and Nationalism (1931-1950). The problems of this study are: (1) factors that influence Muchtar Lutfi's thoughts (2) Muchtar Lutfi's thoughts on Islam and nationalism. The purpose of this study is to analyze the factors that influence Muchtar Lutfi's thoughts and also analyze how Mucthtar Lutfi's Political thoughts. This study was conducted using the philosophical approach method and the historical approach (Historical Approach). The results of the study conducted, the findings of this study conclude; Muchtar Lutfi's thoughts did not happen by themselves. This means that there are those that influence Muchtar Lutfi's thoughts, including the influence of (1) education, (2) the influence of figures and (3) his involvement in various organizations, one of which is the Indonesian Muslim Association (PERMI). Muchtar Lutfi is one of those who helped formulate the understanding of Islam and Nationalism. For Muchtar Luthfi, acceptance of the understanding of nationalism is a logical compromise with other religious elements to fight for Islam together.